Empowering Black boys through a culturally sustaining elementary school book club: Enhancing reading comprehension and academic success - Carrington, Dennis Louis (2025)
Black boys have historically faced significant literacy challenges in educational settings, often due to the lack of culturally sustaining literature that reflects their experiences and identities. This study explored the implementation of culturally sustaining reading clubs as an intervention to address these challenges. Grounded in culturally relevant pedagogy, the initiative provided Black boys with access to literature that resonated with their cultural backgrounds, values, and aspirations. The reading clubs featured a curated selection of texts with Black male protagonists and themes, spanning various genres such as fiction, non-fiction, poetry, and graphic novels. Through interactive discussions, activities, and mentorship, participants engaged with literature in ways that affirmed their identities and fostered a deeper appreciation for reading. The study found that exposure to culturally relevant texts improved reading engagement, comprehension, and self-perception among Black boys. Additionally, the reading clubs created a supportive community where participants could critique, analyze, and celebrate literature in a meaningful way. The initiative demonstrated that culturally responsive literacy instruction could transform reading from a task into an empowering experience, promoting both academic success and self-confidence. The findings underscored the need for educators to integrate culturally relevant materials into literacy instruction to bridge the gap between students' lived experiences and academic content. This research contributes to ongoing discussions on equitable literacy practices and highlights the transformative potential of culturally sustaining pedagogy in addressing literacy disparities among Black boys.